Metacognitive Awareness Scale, Domain Specific (MCAS-DS): Assessing Metacognitive Awareness During Raven’s Progressive Matrices - Song, John H. H.; Loyal, Sasha; Lond, Benjamin (Frontiers in Psychology, 2021)
Metacognition, the cognition about cognition, is closely linked to intelligence and therefore understanding the metacognitive processes underlying intelligence test performance, specifically on Raven’s Progressive Matrices, could help advance the knowledge about intelligence. The measurement of metacognition, is often done using domain-general offline questionnaires or domain-specific online think-aloud protocols. This study aimed to investigate the relationship between metacognitive awareness and intelligence via the design and use of a novel Meta-Cognitive Awareness Scale – Domain Specific (MCAS-DS) that encourages reflection of task strategy processes. This domain-specific scale was first constructed to measure participants’ awareness of their own metacognition linked to Raven’s Progressive Matrices (SPM). Following discriminatory index, Exploratory Factor Analysis, a 15-item scale was devised. Exploratory Factor Analysis showed five factors: Awareness of Engagement in Self-Monitoring, Awareness of Own Ability, Awareness of Responding Speed/Time, Awareness of Alternative Solutions and Awareness of Requisite Problem-Solving Resources. The intelligence level of ninety-eight adults was then estimated using Raven’s Standard Progressive Matrices. Participants also completed the MCAS-DS, and further items that examined their test-taking behaviour and Confidence level. Metacognitive awareness was positively correlated to standardized IQ scores derived from the SPM whilst Over-Confidence derived using the Confidence level measure was negatively correlated to SPM. Despite some limitations, this study shows promise for elucidating the relationship between metacognitive awareness and intelligence using the task-specific scale.